2020
DOI: 10.7759/cureus.8441
|View full text |Cite
|
Sign up to set email alerts
|

Publication Productivity Among Academic Orthopaedic Surgeons in Canada

Abstract: The Hirsch Index (h-index) and m-index are often utilized to assess academic productivity and have been widely found to have a positive association with academic promotion and grant selection. The aim of this study was to assess the relationship between these indices and academic ranks among Canadian orthopaedic surgery faculty members. MethodsFive hundred and sixty-seven Canadian orthopaedic surgery faculty members associated with residency training programs were included in the study. H-indices of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…The advantage of the H-index is that it provides a single number to indicate surgeons’ productivity and mitigates the skewed appearance of academic productivity that occurs when a small number of publications have a large number of citations, and vice-versa. Multiple studies have proven that academic productivity is associated with academic promotion [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. It has been shown that the H-index offers better validity than other bibliometric indices of research performance in the surgical field [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of the H-index is that it provides a single number to indicate surgeons’ productivity and mitigates the skewed appearance of academic productivity that occurs when a small number of publications have a large number of citations, and vice-versa. Multiple studies have proven that academic productivity is associated with academic promotion [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. It has been shown that the H-index offers better validity than other bibliometric indices of research performance in the surgical field [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have found that women in academic surgery are less likely to advance from assistant professor to associate professor 21 . A recent Canadian study explored the role of orthopaedic subspecialty and academic rank on the h-index and found that there were differences in the h-index among the various subspecialties 22 . However, to our knowledge, there has been no analysis of the role that orthopaedic subspecialty selection plays in academic promotion or the differences in research productivity among the various subspecialties in the United States.…”
mentioning
confidence: 99%
“…Hirsch noted that for researchers in traditional subfields of physics a value for h of 12 is typical for promotion to associate professor at major US research universities, and a value of 18 is typical for promotion to full professor 5 . Multiple studies have been performed examining bibliometric benchmarks for various medical specialties 4,7–9 . A meta‐analysis was performed in 2020 that included data on 14 567 academic physicians 10 .…”
Section: Introductionmentioning
confidence: 99%
“… 5 Multiple studies have been performed examining bibliometric benchmarks for various medical specialties. 4 , 7 , 8 , 9 A meta‐analysis was performed in 2020 that included data on 14 567 academic physicians. 10 In this study, it was shown that the h‐index increases with academic rank with a mean h‐index of 5.2 for assistant professors, 11.2 for associate professors, and 20.8 for full professors.…”
Section: Introductionmentioning
confidence: 99%